2019
DOI: 10.1371/journal.pone.0224811
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts affect tolerance of Drosophila melanogaster to food substrate with high NaCl concentration

Abstract: The ability of model animal species, such as Drosophila melanogaster, to adapt quickly to various adverse conditions has been shown in many experimental evolution studies. It is usually assumed by default that such adaptation is due to changes in the gene pool of the studied population of macroorganisms. At the same time, it is known that microbiome can influence biological processes in macroorganisms. In order to assess the possible impact of microbiome on adaptation, we performed an evolutionary experiment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…The diversity and abundance of yeasts in flies tend to increase with the rising salt concentration [Figure 3A, triangles; Table 1]. This is in accordance with previous findings that certain yeast species may help D. melanogaster adapt to elevated salt concentrations [41] .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The diversity and abundance of yeasts in flies tend to increase with the rising salt concentration [Figure 3A, triangles; Table 1]. This is in accordance with previous findings that certain yeast species may help D. melanogaster adapt to elevated salt concentrations [41] .…”
Section: Discussionsupporting
confidence: 89%
“…This aligns with the observation that, with the increase in salt concentration, the percentage of Acetobacter (which can be beneficial for flies) decreased, while the proportion of lactic acid bacteria (also potentially helpful) first increased (from 0% to 4% NaCl), and then drastically decreased at 7% NaCl. It is also in line with the presence of Starmerella yeasts in the fly microbiome at high NaCl concentrations, previously shown to help flies survive and reproduce on the salty substrate [ 42 , 44 ] . These yeasts may also assist the flies in resisting potentially pathogenic bacteria, such as Leuconostoc and Providencia , whose percentage increased at higher salinity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Previous studies have shown that feeding a high‐fat diet (adding coconut oil, for example) to flies 60,61 or high‐sugar supplementations 62,63 to model T2D and insulin resistance, elicits an obese phenotype with decreased lifespan and fecundity, elevated triglycerides and reduced cardiac function 8,15,64‐66 . The effect of sodium chloride in Drosophila has mostly been studied in the context of salt stress and taste perception, with concentrations above 2% shown to negatively impact fly survival and concentrations higher than 4% proving fatal to both larvae and adults 17‐19,21,67 . Interestingly, we observed significant sexual dimorphism in responses of flies to different diets.…”
Section: Discussionmentioning
confidence: 65%